2012
DOI: 10.1111/j.1559-1816.2012.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioral Responses to Workplace Incivility and the Impact of Hierarchical Status

Abstract: Using appraisal theory, this research examined targets' emotional responses to workplace incivility, and how these responses impact targets' behavioral responses. Targets who reported greater incivility reported greater anger, fear, and sadness. Targets' anger was associated with more direct aggression against the instigators; targets' fear was associated with indirect aggression against instigators, absenteeism, and exit; and targets' sadness was associated with absenteeism. Status moderated the effects of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
232
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(243 citation statements)
references
References 90 publications
2
232
1
8
Order By: Relevance
“…As Andersson and Pearson (1999) theorize about a spiral of negative actions in the workplace, where behavior becomes contagious in a 'tit for tat' manner and employees retaliate and reciprocate uncivil behavior, a more concrete exploration of this theoretical frame is warranted. Some support has been shown for this theory, as Porath and Pearson (2012) found that being targeted by aggressive behavior relate, indirectly via anger and fear, to negative behaviors aimed at the instigator. One study directly ties incivility experiences to incivility perpetration among both men and women (Gallus et al, 2014).…”
Section: Negative Outcomes Of Experienced and Witnessed Incivilitymentioning
confidence: 97%
“…As Andersson and Pearson (1999) theorize about a spiral of negative actions in the workplace, where behavior becomes contagious in a 'tit for tat' manner and employees retaliate and reciprocate uncivil behavior, a more concrete exploration of this theoretical frame is warranted. Some support has been shown for this theory, as Porath and Pearson (2012) found that being targeted by aggressive behavior relate, indirectly via anger and fear, to negative behaviors aimed at the instigator. One study directly ties incivility experiences to incivility perpetration among both men and women (Gallus et al, 2014).…”
Section: Negative Outcomes Of Experienced and Witnessed Incivilitymentioning
confidence: 97%
“…When employees must deal with a de-energizing colleague, they may dread it, ruminate about future interactions, and feel their creativity or initiative is inhibited (Porath & Pearson, 2012).…”
Section: Theoretical Underpinnings For Hypotheses On De-energizing Rementioning
confidence: 99%
“…Furthermore, research has also found that frightening appraisals of sexual harassment more strongly mediate the relationship between sexual harassment and psychological well-being than bothersome harassment appraisals, a less intense response (Settles et al, 2011). Other research has found that fear appraisals mediate the relationship between workplace sexual harassment/violence and affective commitment and turnover intentions (Barling et al, 2001), and between incivility and absenteeism and turnover (Porath & Pearson, 2012). Thus, focusing on frightening appraisals may be especially important for understanding when negative outcomes will result from sexual harassment experiences.…”
Section: Dimensionality Of Sexual Harassment Appraisalsmentioning
confidence: 99%